KAJIAN HUKUM PIDANA TERHADAP TINDAK PIDANA PEMBUNUHAN TERENCANA DISERTAI PEMERKOSAAN SEBAGAI CONCURSUS REALIS (Studi Putusan Pengadilan Negeri Surabaya No. 1379/Pid.B/2005/Pn.Sby) - Purba, Purwanto; Santoso, Oki Budi (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2013)
AbstractThat this research aims to determine the application of the concursus setting in rape and murder crime in Case Decision No. 1379/Pid.B/2005/PN.Sby and consideration of the judges in criminal of murder that preceded the crime of rape in Case Decision No.1379/Pid.B/2005/PN.Sby.The research method used in the writing of this law are as follows: type of normative research, the nature of prescriptive research, case study approach, qualitative research methods, data analysis techniques to the deduction method, the collection of legal materials to the library and the secondary legal materials (text books written by legal experts, law journals, opinions of scholars, scientific works, papers, and magazines), tertiary legal materials (dictionaries and the Internet), and legal research sources of primary legal materials consist of legislation, record- official records or minutes in the making of legislation and the decisions of judges and secondary legal materials in the form of all the publicity about the law that are not official documents. Publication of the law include text books, law dictionaries, law journals, and the comments of the decision by the court.Based on this research can be concluded, the crime of rape with homicide is an act of deed unison. Rape as a criminal offense under Article 285 of the Criminal Code is: “ Whoever by force or by threat of force a woman not his wife have intercourse with him, because of rape, shall be punished with imprisonment for twelve years”. Element behavior “taking the life” of others, show that the crime of murder is a substantive criminal offense, which is a criminal offense that prohibits certain consequences (as a result of prohibited or due to constitutive / constitutief gevolg). Judge’s decision is in conformity with the act of deed unison (Concursus Realist or Meerdaadse Samenloop). Because the deed is done by unison with continuing act the decision imposition was already in accordance with the concepts and theories of criminal law and in accordance with concursus that is the basis for consideration. The judge in the decision of justice in Case Decision No. 1379/Pid.B/2005/PN.Sby he decided by a panel of judges with a second charge then it is true that the Public Prosecutor to use Article 340 of the Criminal Code article 338 of the Criminal Code subsidiary; Article 285 of the Criminal Code; Article 2 paragraph (1) of Law No. 12 of 1951.Keywords: Rape, Murder, Deeds Unison.